2019
DOI: 10.1037/trm0000179
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver self-reports and reporting of their preschoolers’ trauma exposure: Discordance across assessment methods.

Abstract: Nearly half of preschool-aged children from low-income families in the United States have been exposed to potentially traumatic events (PTEs), yet few are identified or receive trauma-focused mental health care. Given the critical need to accurately and efficiently identify PTE-exposed individuals, the current study examined discordant caregiver self-reporting of PTE exposure and caregiver reporting of child PTE exposure across two assessment methods: checklist and interview. Research has demonstrated signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…These findings demonstrating concordance values that fall predominantly in the fair-to-moderate range for both overall endorsement and endorsement of characteristics of specific ALE types align with some of the general grouping patterns observed in prior studies on concordance between interview and questionnaire formats. For example, Glackin et al (2019) reported kappa values between interview and questionnaire formats for any type of ALE and indirect violence to be in the fair range, whereas exposure to noninterpersonal violence was in the poor range. The present data extend these prior findings by demonstrating this variability at the level of the individual type of ALE exposure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These findings demonstrating concordance values that fall predominantly in the fair-to-moderate range for both overall endorsement and endorsement of characteristics of specific ALE types align with some of the general grouping patterns observed in prior studies on concordance between interview and questionnaire formats. For example, Glackin et al (2019) reported kappa values between interview and questionnaire formats for any type of ALE and indirect violence to be in the fair range, whereas exposure to noninterpersonal violence was in the poor range. The present data extend these prior findings by demonstrating this variability at the level of the individual type of ALE exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Among these studies, two found strong, positive correlations between formats on the overall number of reported ALEs, suggesting reliability between formats (Allen et al, 2012;Wagner et al, 2006). Glackin et al (2019) found agreement between questionnaire versus interview methods to range between 10.9% and 45.3% for certain ALE groupings, with Cohen's kappa estimates reaching a max of .36.…”
Section: Abstract Childhood Adversity Stress Children Assessment Meth...mentioning
confidence: 99%
See 2 more Smart Citations
“…We did not measure caregiver and child reports of different trauma types across different assessment methods, nor did we have information about how the screening was conducted. A study comparing discordance among caregiver-child reports across assessment methods found that caregivers generally reported higher levels of self-exposure to PTEs as well as child PTEs via interview as compared to checklists, with the exception of higher report frequencies of both caregiver and child direct violence exposure through checklists than through interview (Glackin et al, 2019 ). Based on this, Glackin et al ( 2019 ) suggested that caregivers may feel more comfortable disclosing severe PTE exposure via checklists rather than through interviews.…”
Section: Discussionmentioning
confidence: 99%